Remittances, capital flows and financial development during the mass migration period, 1870-1913. - Esteves, R; Khoudour-Castéras, D (Cambridge University Press, 2011)
This article addresses the question whether the substantial financial flows received by emigration countries contributed to domestic financial development in peripheral Europe before 1914. We quantify a sizable and significant relation between remittances and measures of financial development that is both larger than the contribution of other international capital flows and the best estimates of the same relation today. Given that financial development is regularly included among the conditions for economic growth and catch-up of developing nations, this article adds to our understanding of the multiple impacts of the mass migration phenomenon on the economies of emigration countries.